Analisis Yuridis Tanggung Jawab KOMDIGI terhadap Kebocoran Data Pribadi Berdasarkan Undang-Undang Perlindungan Data Pribadi: A Juridical Analysis of KOMDIGI’s Liability for Personal Data Breaches Under the Personal Data Protection Law - Ady Kriesna; Siti Marwiyah; Noenik Soekorini; Sri Astutik (Constitution Journal, 2026)
The Ministry of Communication and Digital (Komdigi), as the manager of the country's personal data, is responsible for the security of digital infrastructure through the implementation of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). The purpose of this study is to identify data breaches within the Ministry. The purpose is to analyze the policies of government officials within the Ministry as a form of accountability for government agencies regarding data breaches under the PDP Law. This study uses a normative research method. The legal material collection procedure in this study is a literature review. The results indicate that factors causing data breaches include human error, IT system weaknesses, and a lack of cyber audits, such as the 2023 case that affected 1.3 million users. Officials' responsibilities are regulated in Article 55 of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law), which concerns data security due diligence, with administrative sanctions ranging from fines to criminal penalties or dismissal. Implementation still faces challenges such as a lack of cyber human resource training and cross-agency coordination Abstrak Kementerian Komunikasi dan Digital (Komdigi) selaku pengelola data pribadi negara bertanggung jawab atas keamanan infrastruktur digital melalui penerapan Undang-Undang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi (UU PDP). Tujuan penelitian ini adalah untuk mengidentifikasi celah kebocoran data di Kementerian Komdigi. Untuk menganalisis kebijakan pejabat pemerintahan di Kementerian Komdigi sebagai bentuk tanggung jawab lembaga pemerintahan terkait kebocoran data berdasarkan UU PDP. Penelitian ini menggunakan metode penelitian normatif. Prosedur pengumpulan bahan hukum dalam penelitian ini yaitu kajian literatur atau studi kepustakaan. Hasil penelitian menunjukkan bahwa faktor penyebab kebocoran data meliputi kelalaian manusia, kelemahan sistem TI, minimnya audit siber, seperti kasus 2023 yang menyasar 1,3 juta pengguna. Tanggung jawab pejabat diatur dalam Pasal 55 Undang-Undang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi (UU PDP) tentang due diligence pengamanan data, dengan sanksi administratif hingga pidana berupa denda atau pemecatan. Implementasi masih menghadapi tantangan seperti kurangnya pelatihan SDM siber dan koordinasi lintas instansi.